Emotional Education in the Qur'an: Narrative Analysis of Stories of Qur'anic Decisions in Islamic Education - Ekawati Hamzah; Indo Santalia; Lailatul Qoimah (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
Until now, the world of education tends to be dominated by the concept of intellectual intelligence (IQ) both in theory and practice, while the aspect of emotional intelligence (EQ) is often neglected. However, in the context of Islamic education, emotional intelligence is a crucial foundation for forming individuals who are knowledgeable and have noble morals according to the guidance of sharia. Therefore, this study aims to explore the dimensions of emotional intelligence in the Qur'an through the narratives of the Prophet Moses, the Prophet Joseph, and Luqman al-Hakim. The focus of this study is to analyze how these figures manage emotional stress, make decisions, and carry out leadership and guidance effectively. This study uses a qualitative approach with a narrative-thematic analysis method and a maudū'i (thematic) interpretation approach. Through this technique, patterns of emotional education are identified from the Qur'anic texts to see their relevance to modern Islamic psychopedagogy. The research findings show that the Qur'an not only contains cognitive and spiritual aspects but also provides a comprehensive affective structure in the Islamic learning process. The stories of the prophets provide concrete models of self-regulation, empathy, and mental resilience, which are at the heart of emotional intelligence. This research significantly contributes to the development of a revelation-based character education curriculum. The results can serve as a theoretical foundation for educational practitioners in designing learning models that integrate emotional and spiritual intelligence contextually.